AUGMENTED REALITY HYDRANT PEMADAM KEBAKARAN BERBASIS ANDROID - Putri Sintya Dewi; Made Sudarma; Duman Care Khrisne (Jurnal SPEKTRUM, 2020)
Augmented Reality (AR) is a technology used to display a 3-dimensional animatedobject with marker as a medium for displaying 3-dimensional animation in real time. AugmentedReality Hydrant for Fire Extinguishers Based on Android is an application used for learningmedia in the introduction of fire extinguishers with the aim of making it easier for the public orfirefighters to find out their form and function through this application. The Fire ExtinguisherHydrant Augmented Reality application is made in several stages, namely identifying problems,determining goals and objectives, analyzing needs, designing systems, designing designs,making systems and testing systems. This Android-based Augmented Reality Hydrant candisplay several Hydrant objects or Fire Extinguishers and display information about theseobjects.